(untitled) (Филолошки студии, 2021)
This work has the goal to describe and analyze notes dedicated to literary periodicals, that Tihomir Ostojić has been intensively publishing in the magazine “Stražilovo” at the end of the XIX century, as well as the notes that this historian of literature published in “Letopis Matice srpske” between 1900 and 1914. Small in size, not so big in scope, but easy to go through, informative, communicative, immanently valuable, and solely in the magazine form, everyday information, and additional information about that moment in literature, Tihomir Ostojić’s notes published in “Stražilovo” and “Letopis Matice srpske” give us a way to see the literary scene of that time. They are full of information useful for getting to know the history of Serbian literature and culture; on the other hand, these notes about literary periodicals are useful for reading and understanding Tihomir Ostojić’s autopoetics.